PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA PRAJURIT DI MAPUSPALAD - Wibowo, Wuryanto; Faeni, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to provide evidence regarding the influence of organizational culture and competency on Soldier Performance in Mapuspalad. The variables measured are organizational culture (X1), competency (X2) and performance (Y). The sample used in this research was Soldiers in Mapuspalad. The sampling method used was saturated sampling. Saturated sampling uses a relatively small population even though both use the entire population as a sample. (Sugiyono, 2017:122). The data used is primary data using a questionnaire, with a sample of 105 Soldiers in Mapuspalad as respondents. The analysis carried out was multiple linear regression analysis, f-test and simple t-test. From the results of this research, it was found that the f-test was 11.006 > f-table 1.665 and the significance was 0.000 < 0.05, so organizational culture and competence had a positive and significant effect on the performance of Soldiers in Mapuspalad. The calculated t-test results of the organizational culture variable (X1) are 4.074 > t-table 1.665 and sig 0.000 with the results having a positive and significant effect on the performance of Soldiers in Mapuspalad while the t-calculated competency (X2) is 2.832 > t-table 1.665 and significant 0.006, with the results having a positive and significant effect on the performance of Soldiers in Mapuspalad.